2021
DOI: 10.2196/preprints.31847
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effects of Internet Exposure on Sexual Risk Behavior Among Sexually Experienced Male College Students in China: Cross-sectional Study (Preprint)

Abstract: BACKGROUND As a young subgroup, college students have become the main users of mobile social networks. Considering that people can indiscriminately access explicit sexual content on the internet, coupled with the increase of HIV infections in male college students, the role of the internet in meeting sexual partners and its correlation to risky sexual behavior has become an important topic. OBJECTIVE … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…This study found no statistical difference between the commercial sex behavior group and the noncommercial sex behavior group in terms of temporary heterosexual sex partners, but 50.5% of the commercial sex behavior group used the Internet to find temporary partners, which was 2.58 times that of the noncommercial sex behavior group. With the popularization of the Internet, some young students can easily find sexual partners and have unprotected sex [27]. This has increased challenges in HIV/AIDS prevention and control, leading to growing concerns regarding HIV transmission [28].…”
Section: Discussionmentioning
confidence: 99%
“…This study found no statistical difference between the commercial sex behavior group and the noncommercial sex behavior group in terms of temporary heterosexual sex partners, but 50.5% of the commercial sex behavior group used the Internet to find temporary partners, which was 2.58 times that of the noncommercial sex behavior group. With the popularization of the Internet, some young students can easily find sexual partners and have unprotected sex [27]. This has increased challenges in HIV/AIDS prevention and control, leading to growing concerns regarding HIV transmission [28].…”
Section: Discussionmentioning
confidence: 99%